Curriculum framework for employability readiness skills: sustainable industry engagement - A Azman Arshad; Roseman Mat Jidin; Mohd Firdauz Mhd Radzi (RedWhite Press, 2020)
In spite of endeavors to expand the idea of graduate employability, there stays an overall spotlight on creating industry-pertinent employability abilities. The Work- Based Learning approach is found completely catch the multifaceted nature of graduate work-availability. This paper contends for the reclassifying of graduate employability by grasping industrial skills development and identifies with a comprehension of and association with the aptitudes, characteristics, lead, culture and belief system of an expected calling. The partnership model is attracted upon to show how WBL can be designed and created during internship by involving curriculum reform and mapping. The aim of this study is to reduce the skills gap between institution and industry by designing additional curriculum. These programmes are viewed as significant in light of the fact that they encourage students’ access to work-based learning activities in polytechnics and work-based opportunities such as placements after completed the internship.